Analysis of the Balance of Value and Weight of Exports Indonesia : Analisis Keseimbangan Nilai dan Berat Ekspor Indonesia - Suprianto, Suprianto; A., Ade Ayu Fitriana; Rahmawati, Eka Fauziah; Prayoga, Mirza Kirma (Indonesian Journal of Innovation Studies, 2026)
Indonesia's export performance is still less than optimal because the leading commodities are dominated by products with large volumes but relatively low value per unit weight. This study aims to analyze the balance between the value and weight of Indonesia's exports and identify commodity groups based on the characteristics of export value per weight and volume. The data used is Indonesia's cross-sectional export-import data for the period of July 2024, covering 98 commodities based on HS codes, including the variables of export value (USD) and export weight (kg). The method used is agglomerative hierarchical clustering (AHC). The analysis results two main clusters, namely the bulk cluster with high export weight but lower value per volume, consisting of 30 commodities, and the premium cluster, consisting of 68 commodities with smaller export weight but high export value per kg. Commodities in the first cluster should focus more on improving logistics efficiency and export volume, while commodities in the second cluster require support in the form of improved domestic institutions, regulations, and branding strategies to expand market access. These findings emphasize the need for differentiated export policies based on cluster characteristics and indicate the great potential of high-value commodities as the backbone of Indonesia's exports in the future. Highlights: Identifies two main export clusters: bulk and premium commodities. Highlights policy needs based on export value-to-weight characteristics. Emphasizes potential of high-value commodities for future export growth. Keywords: export value, export weight, hierarchical clustering, internasional trade